(untitled) (HEALTH CARE: JURNAL KESEHATAN, 2026)
Breastfeeding success among adolescent mothers is influenced by several factors, one of which is Breastfeeding Self-Efficacy (BSE), defined as a mother’s confidence in her ability to breastfeed. Adolescent mothers often face physical, psychological, and social challenges that may affect breastfeeding practices. This study aimed to describe BSE among breastfeeding adolescent mothers in Padang Panjang City. The type of this research is descriptive quantitative study involved 156 adolescent mothers selected through consequtive sampling. Data were collected using a respondent characteristics questionnaire and the Breastfeeding Self-Efficacy Scale-Short Form (BSES-SF). Data were analyzed using univariate analysis and presented as frequency distributions and percentages. The result of this study was the most respondents were aged 17–19 years, had completed senior high school education, delivered vaginally, and were unemployed. The findings revealed that the majority of adolescent mothers had a high level of BSE. In conlucsion, adolescent mothers in Padang Panjang City demonstrated high breastfeeding self-efficacy, indicating strong confidence in their breastfeeding abilities. These findings highlight the importance of sustaining and strengthening adolescent mothers’ confidence through continuous breastfeeding education and support programs provided by healthcare professionals.